Issues for a Neo-Polanyian Research Agenda in Economic Sociology - Randles, Sally (International Review of Sociology, 2003)
Kari Polanyi Levitt has commented that her father's writing was met with a 'deafening silence' in England, a silence which she suggests is 'yet to be explained'. Given The Great Transformation was purposefully, situated in England Polanyi Levitt's point is an interesting one, and one which still deserves attention. But the last two decades have witnessed an intensification of interest in Karl Polanyi's methodological approach and theoretical insights, from England as well as elsewhere, and representing a range of disciplines. This raises a string of associated questions: interest from who? Why now? And how? Further we could ask: Does this new interest have the potential to redress the Polanyi Levitt charge without falling prey to an opposite one of misusing or abusing the Polanyi legacy? This paper contributes to the much larger agenda of examining in a serious way the usefulness and applicability of Polanyi's key ideas and methods, particularly as they apply to the burgeoning interest in markets and exchange within New Economic Sociology (NES). A sub-set of this agenda is to explore whether Polanyian insights provide a more nuanced and critical understanding of competitive processes and innovation than is currently available within Economics, Sociology or indeed Economic Sociology.
Keywords: England; Great Transformation, The (Book); POLANYI LEVITT, Kari; POLANYI, Karl, 1886-1964; Polanyi's legacy; economic sociology; economics; socioeconomics; sociology

Karl Polanyi: New Perspectives on the Place of the Economy in Society - Harvey, Mark; Ramlogan, Ronnie; Randles, Sally (Oxford University Press, 2014)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology and social policy. Newly available in paperback, this volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. Several of the contributions develop Polanyian ideas in relation to contemporary capitalism. However, in a critical spirit, other contributions in the volume substantially transform his concept 'instituted economic process' in considering a broad range of contemporary socio-economic change: markets for mobile telephony, call centre operations and European labour markets.
Keywords: business & economics; economic theory

Nano-worlds as Schumpeterian emergence and Polanyian double-movements - Randles, Sally; Dewick, Paul; Loveridge, Denis; Schmidt, Jan C. (Technology Analysis & Strategic Management, 2008)
The overarching question raised in this special issue is whether societies can, do or indeed should steer new and emergent science and technological development and its management on to trajectories construed as more or less 'desirable'. It therefore sits at the interface of two arenas. These are governance: processes of shaping/steering emergent technologies and markets; and sustainability: normative agendas incorporating a range of potentially competing conjectures and internally inconsistent desires such as to facilitate rather than stifle innovation, to enable economic development, to anticipate or deploy strategies to cope with risk and uncertainty, and to encourage technological developments that benefit rather than harm humans, their quality of life and the natural environment. Despite the potential for apparent empirical inconsistencies and contradictions that manifest as outcomes of the negotiation of these aims, there is (pace Karl Polanyi) a normative entry point to all of the articles and the material they draw upon, which is the idea that markets and technologies should be the handmaiden of societies, not vice versa. It is now widely recognized that 'nanotechnology' is a diverse set of feasible procedures emerging from scientific possibilities to enable the production of artefacts at the nanoscale creating new products, processes and services. Attention has to be paid to the desirability of these artefacts, which involve social, economic, ecologic, political and ethical matters that surround their emergence. The purpose of this special issue is to set out the current and future prospects for the widespread use (or innovation) of technological convergence at the nanoscale to create nano-artefacts, and the needs for governance and regulation that will accompany these innovations.
Keywords: POLANYI, Karl, 1886-1964; SCHUMPETER, Joseph Alois, 1883-1950; double movement; economic development; editorials; emergence; governance; nano-; nanotechnology; new product development; quality of life; sustainability; technological innovations